EMOQuest : best practice visual emotional techniques survey in teaching and learning as an innovative approaches using mobile applications / Fadila Mohd Yusof, Azhari Md Hashim and Azmir Mamat Nawi - Mohd Yusof, Fadila; Md Hashim, Azhari; Mamat Nawi, Azmir (Universiti Teknologi MARA, Kedah, 2019)
EMOQuest Apps is visual images of emotions questionnaires develop through mobile application to conduct a survey. Questionnaires is a research instruments consisting of series of questions develop for the purpose of gathering information from respondent. The information gathered must be quickly answered, precised and met the respondent expectation without hassle them to read and deeply understand the question given. This innovative survey method is useful to access respondent without limiting their time and provide a quick response towards the questionnaires. The use of mobile apps would encougared more users to use this type of surveys and easier for them to analyse the data and make the session more interesting and digitialise. This type of method would be useful for students to conduct a survey for their assignment and provide reliable data as well as immediate response through smart mobile telephone without the hassle of reading and to deeply understand the questions provide during the survey. It will also serve as a survey template and easier for student to design the survey according to their proposed study. This innovative method will make the teaching and learning activity more easier and variety as well as saving student time frame during the academic semester.